Profile of Obstetric Morbidity Among Maternal Intensive Care Unit Patients - Shakya, B; Chaudhary, P; Tumbahangphe, M (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The objective of the study was to determine the outcome of the obstetric admissions to Maternal Intensive Care Unit in the setting of a tertiary care hospital. Methods: This was a cross-sectional study undertaken at Paropakar Maternity and Women’s Hospital from April 1, 2012 to March 31, 2013. Patient characteristics, gestational age, booking status, indication for intensive care unit admission, intervention, length of stay and outcome were analyzed. Results: During the study period, 19,247 deliveries occurred and 247 women were admitted to maternal intensive care unit. This accounts for 1.28% of all deliveries. The most common indication of admission to intensive care unit was hypertensive disorders in pregnancy (45.3%) followed by obstetric hemorrhage (39.27%). Sepsis was the cause in ten (4.04%) cases. Ten cases (4.04%) of postpartum hemorrhage were managed by balloon tamponade, seven (2.83%) by B-Lynch compression sutures and three (1.21%) necessitated cesarean hysterectomy. Among 18 cases of ruptured uterus, 13 (5.26%) were repaired while five (2.02%) required hysterectomy. Maternal mortality occurred in four (1.61%) of the cases. One was a case of severe preeclampsia who died on 4th post-operative day due to pulmonary embolism, another due to anesthetic complication and the other two died of septic shock and multiorgan failure. Conclusions: Hypertensive disorders of pregnancy and obstetric hemorrhage appeared as the major risk factors for admission to an intensive care unit thereby influencing maternal outcomes in obstetric patients. DOI: http://dx.doi.org/10.3126/njog.v9i2.11762